Strategies for HIV-1 suppression through key genes and cell therapy - Sorokina, Alyona; Anchakova, Elizaveta; Dashinimaev, Erdem (Frontiers in Medicine, 2023)
Human immunodeficiency virus type 1 (HIV-1) remains a significant challenge for global public health as limited therapeutic options are available for HIV-infected individuals receiving combination antiretroviral therapy. Additionally, individuals with HIV-1/acquired immunodeficiency syndrome (AIDS) complications have a reduced life expectancy. In recent decades, gene and cell-based strategies have shown promise in achieving a functional cure for HIV-1 infection. The outcomes of therapies with patients in Berlin and London have led to moderate optimism for a highly effective HIV-1 treatment. This review categorizes current strategies for HIV-1 treatment into RNA- and antibody-based therapies, cell and genome editing approaches, and methods for eradicating latent reservoirs. These findings demonstrate how the use of various anti-HIV-1 agents enhances our understanding of HIV-1 infection and may provide important insights for potential HIV-1 treatment.